2012
DOI: 10.1103/physreve.86.051117
|View full text |Cite
|
Sign up to set email alerts
|

Geodesics in information geometry: Classical and quantum phase transitions

Abstract: We study geodesics on the parameter manifold, for systems exhibiting second order classical and quantum phase transitions. The coupled non-linear geodesic equations are solved numerically for a variety of models which show such phase transitions, in the thermodynamic limit. It is established that both in the classical as well as in the quantum case, geodesics are confined to a single phase, and exhibit turning behavior near critical points. Our results are indicative of a geometric universality in widely diffe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…[103]) and a geodesic-analysis (for more details, see Ref. [111]) were considered for this specific model. The geometric parameters used in this case were the anisotropy parameter γ and the magnetic field intensity h. For this system the components of the metric tensor on the parameter manifold diverge at the quantum phase transition, while the Ricci scalar curvature does not (see Eqs.…”
Section: Quantum Frameworkmentioning
confidence: 99%
“…[103]) and a geodesic-analysis (for more details, see Ref. [111]) were considered for this specific model. The geometric parameters used in this case were the anisotropy parameter γ and the magnetic field intensity h. For this system the components of the metric tensor on the parameter manifold diverge at the quantum phase transition, while the Ricci scalar curvature does not (see Eqs.…”
Section: Quantum Frameworkmentioning
confidence: 99%
“…In a different context, pioneering efforts by Ruppeiner and others have shown that the equilibrium state space of a thermodynamic system can be uplifted to a Riemannian geometry via the Gaussian fluctuation moments which constitute the metric [10]. Thermodynamic geometry has been investigated for a variety of systems ranging from fluids and magnetic systems to various black hole systems, and significant information has been revealed through the invariants of the geometry, like the geodesics or the curvature scalar [10][11][12][13][14][15]. Thermodynamic geometry forms a remarkable connection from the thermodynamic description to the underlying statistical description.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest in these studies is the role of the scalar (Riemannian) curvature. It was shown to diverge at critical transition points and on the spinodal curve [25,26], thus effectively preventing geodesics from crossing into the unphysical area of phase space [27]. See also [28] for a general renormalization group analysis of IG near criticality.…”
Section: Introductionmentioning
confidence: 99%